2014
DOI: 10.1016/j.ajhg.2013.12.014
|View full text |Cite|
|
Sign up to set email alerts
|

Causal Effects of Body Mass Index on Cardiometabolic Traits and Events: A Mendelian Randomization Analysis

Abstract: Elevated body mass index (BMI) associates with cardiometabolic traits on observational analysis, yet the underlying causal relationships remain unclear. We conducted Mendelian randomization analyses by using a genetic score (GS) comprising 14 BMI-associated SNPs from a recent discovery analysis to investigate the causal role of BMI in cardiometabolic traits and events. We used eight population-based cohorts, including 34,538 European-descent individuals (4,407 type 2 diabetes (T2D), 6,073 coronary heart diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
156
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(180 citation statements)
references
References 55 publications
(53 reference statements)
21
156
1
2
Order By: Relevance
“…A Mendelian randomization study showed that BMI-related genetic variants did not increase the CVD or stroke risk despite being associated with multiple cardiometabolic traits, including T2D (41). A previous study (42) of 2,607 NHANES III participants with T2D showed that BMI and measures of adiposity did not predict mortality over 6.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…A Mendelian randomization study showed that BMI-related genetic variants did not increase the CVD or stroke risk despite being associated with multiple cardiometabolic traits, including T2D (41). A previous study (42) of 2,607 NHANES III participants with T2D showed that BMI and measures of adiposity did not predict mortality over 6.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates were obtained from the aforementioned large Danish study 30 —the largest study included in our meta-analysis—and two Mendelian randomization studies 54 , 55 . A detailed description of the simulations is provided in Supplementary Methods (available as Supplementary data at IJE online).…”
Section: Methodsmentioning
confidence: 99%
“…Although previous genetic and heritability studies have demonstrated direct and independent effects on CRP levels(de Maat et al, 2004; Dehghan et al, 2011; Pankow et al, 2001; Wörns et al, 2006), there is evidence suggesting a causal relationship between the genetics of obesity and circulating CRP levels. SNPs associated with body mass index (BMI) can influence blood levels of CRP, while the converse has not been demonstrated (Holmes et al, 2014; Welsh et al, 2010). Thus, to further probe the unique nature and strength of the association between adiposity and IL-6, we also considered the relationship between adiposity and CRP.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between a genetic score, consisting of 14 SNPs related to BMI, and multiple cardiovascular and inflammatory traits including both IL-6 and CRP, were recently assessed (Holmes et al, 2014). However, it is still not known whether the heritable influence of obesity on IL-6 and its soluble receptor are coordinated, and whether CRP is affected in a similarly linked manner.…”
Section: Introductionmentioning
confidence: 99%